1974
DOI: 10.1007/bf01976698
|View full text |Cite
|
Sign up to set email alerts
|

The identification of bean mosaic, pea yellow mosaic and pea necrosis strains of bean yellow mosaic virus

Abstract: Twelve virus isolates from pea, broad bean, red clover and yellow lupin have been compared with the B25 strain of bean yellow mosaic virus (BYMV-B25), the E198 strain of pea mosaic virus (PMV-E198) and the pea necrosis virus (El 78), which were described earlier (Bos, 1970).On the basis of host ranges, symptoms and bean and pea varietal reactions most isolates could be classified into three groups, representatives of which did not differ appreciably serologically. These groups were considered to be typical bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

1977
1977
1992
1992

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 19 publications
5
34
0
Order By: Relevance
“…For instance, some workers regard BYMV and PMV to be strains of the same virus [4,7,20,39], while others consider them as distinct viruses [3,27]. Similarly, BYMV and CYVV are considered by some workers to be strains of the same virus [8,9,20], while others have suggested that they are distinct potyviruses [3,19,27]. These conflicting assignments have been made on the basis of comparative biological and serological properties and from the results of molecular hybridization studies using randomly primed cDNA.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, some workers regard BYMV and PMV to be strains of the same virus [4,7,20,39], while others consider them as distinct viruses [3,27]. Similarly, BYMV and CYVV are considered by some workers to be strains of the same virus [8,9,20], while others have suggested that they are distinct potyviruses [3,19,27]. These conflicting assignments have been made on the basis of comparative biological and serological properties and from the results of molecular hybridization studies using randomly primed cDNA.…”
Section: Discussionmentioning
confidence: 95%
“…Fisher 1953) and red clover necrosis virus, isolated from peas, and was shown to be serologically related to BYMV (Zaumeyer and Goth 1963 (Bos et al 1974) in reacting more strongly with PMV than with BYMV antiserum.…”
mentioning
confidence: 99%
“…Our earlier research had revealed the existence of strains of BYMV which were highly different pathologically, biological overlap of BYMV with CIYVV, and the existence of strains ofBYMV or of a separate virus especially adapted to faba bean [20]. We therefore compared representatives of these new faba bean isolates with isolates earlier identified as BYMV and CIYVV, for their biological and serological properties, and also employed virus-specific antibodies directed towards N-terminal parts of coat proteins [32].…”
Section: Further Complicationsmentioning
confidence: 97%
“…Further studies in our laboratory in the early 1970's allowed the biological differentiation of bean mosaic, pea yellow mosaic, and pea necrosis strains of BYMV [20], the discrimination between the pea necrosis strain of BYMV and the pea necrosis virus [9], and the demonstration that the latter was ClYVV [21]. Through international comparison, pea leafroll mosaic virus was found to be one of the isolates of pea seed-borne mosaic virus which was described during the late 1960's more or less simultaneously with varying names in different parts of the world [41].…”
Section: Fading Borderlines; Continuum Hypothesismentioning
confidence: 99%